2003
DOI: 10.1017/s003118200300369x
|View full text |Cite
|
Sign up to set email alerts
|

The properties of acidic compartments in developing schistosomula ofSchistosoma mansoni

Abstract: A variety of fluorescent probes have been used to study the acidic compartments in cercariae and schistosomula of Schistosoma mansoni. Freshly transformed schistosomula treated with the LysoTracker Red dye specific for lysosomes showed large acid-containing compartments (0.5-10 microm in size). The uptake of the dye is an energy-dependent process that depends on the metabolic activity of schistosomula. The compartments were quantified individually with respect to area, quantity of fluorescence and the total nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Almost all (95%) of Gleevec entering cells (regardless of cell type) becomes sequestered in lysosomes (25,26) through ion trapping, because Gleevec is a weak base (27)(28)(29). To examine the possibility that Gleevec might inhibit the activities of lysosomal proteases by raising lysosomal pH, we exposed N2a 695 cells to vehicle or to Gleevec for 4 h and then to the lysosomotropic dye Lysotracker Red (Thermo Fisher Scientific), which sequesters in acidified lysosomes (30). Gleevec pretreatment increased the amount of Lysotracker Red in lysosomes and also appeared to increase lysosomal volume (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Almost all (95%) of Gleevec entering cells (regardless of cell type) becomes sequestered in lysosomes (25,26) through ion trapping, because Gleevec is a weak base (27)(28)(29). To examine the possibility that Gleevec might inhibit the activities of lysosomal proteases by raising lysosomal pH, we exposed N2a 695 cells to vehicle or to Gleevec for 4 h and then to the lysosomotropic dye Lysotracker Red (Thermo Fisher Scientific), which sequesters in acidified lysosomes (30). Gleevec pretreatment increased the amount of Lysotracker Red in lysosomes and also appeared to increase lysosomal volume (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy is a more feasible process than apoptosis for vitelline cell degradation because almost all of the autophagic components have been found in the transcriptome and autophagy is known to occur in adult schistosomes [42,44,45]. Autophagy eliminates unwanted cells during developmental cell death in various taxa, including the ovarian nurse cells in Bombyx mori and Ceratitis capitata [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Carneiro-Santos et al (2001) demonstrated the presence of acidic organelles similar to lysosomes in schistosomula, as well as the absence of the same organelles in cercariae. These data were confirmed by Al-Adhami et al (2003, 2005. In this latter study, it was also demonstrated that miracidia do not reveal the presence of acidic vesicles when exposed to LysoTracker Red.…”
Section: Discussionmentioning
confidence: 55%
“…In studies using S. mansoni, Al-Adhami et al (2003) ally similar to lysosomes, in schistosomula, and the absence of them in cercariae, by means of the label Lyso Tracker Red, specific for lysosomes of mammal cells (Dietl et al 1996). In another study, Al-Adhami et al (2005) observed the presence of large acidic organelles in immature worms (lung stage), but not in adult worms and miracidia.…”
mentioning
confidence: 96%